A GLIMPSE ON THE TRIBULATIONS OF TEACHING ENGLISH IN HIGHER EDUCATION - GANEA, Marcela (PEOPLE: International Journal of Social Sciences, 2018)
This paper has aimed at identifying the main hindrances during the process of teaching/learning English language. The findings result from data collected in a university with heterogeneous levels of proficiency in English and a wide range of attitudes towards learning. I have found that most students are not aware of the distracting factors that prevent them from achieving academic performance: the smartphone, romantic relationships, distraction to other sites instead of work, lack of personal discipline, etc. Students are not aware that the learning process is complex and they overlook: the need to combine individual study and class work, the role of the teachers to detect the students’ needs and difficulties and to provide feedback, the difference in learning skills, the affective barriers and inhibitions, the lack of ambition and the lack of ability to organize time and resources efficiently.What I found useful after 5 years of teaching is a 30-page Handbook for English Students designed in such a manner so that it should raise awareness about all the above mentioned aspects and instruct students how to combine individual study with teamwork, how and where to find info, and how to manage time.Teachers should keep in mind that higher education in today’s digitalized world is operating more on constructivism and less on cognitivism. It means that the teacher will mainly make efforts to teach the students how to learn and where to get information from, and what to learn, depending on each student’s needs.